2018
DOI: 10.1080/21645515.2018.1536587
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in vaccination counselling: a survey on the impact of a three-day residential course

Abstract: Background : In an era of hesitance to use vaccines, the importance of effective communication for increasing vaccine acceptance is well known. This study aimed to assess the impact of a three-day residential course concerning empathy and counselling abilities on patients’ ratings of the level of empathy of physicians and nurses working in vaccination centers. Methods : The empathy of healthcare providers was evaluated using the Adapted Consultation and Relational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Response rate (84.6%) was consistent with literature data: in a recent study published by Regan A.K. et al, response rate to text messaging and oral voice telephone interviews for AEFIs detection ranged between 63.9% and 90.1%, depending on the age and sociodemographic characteristics of the enrolled people [36,37].…”
Section: Discussionsupporting
confidence: 87%
“…Response rate (84.6%) was consistent with literature data: in a recent study published by Regan A.K. et al, response rate to text messaging and oral voice telephone interviews for AEFIs detection ranged between 63.9% and 90.1%, depending on the age and sociodemographic characteristics of the enrolled people [36,37].…”
Section: Discussionsupporting
confidence: 87%
“…One of the strengths of our study is the value of the response rate (94%), which is higher than the one reported by similar studies (ranging from 63% to 90%) [ 24 , 25 ]. Moreover, the homogeneous sample allowed studying the safety of the vaccine on a specific subgroup population.…”
Section: Discussionmentioning
confidence: 52%
“…To this end, it is important to highlight that emotional competences are conceptualized as abilities that can be taught and learned [ 20 ]. Some findings suggest that healthcare professionals can improve their empathy in vaccination counselling sessions [ 52 ] and that dialogue-based interventions that embrace parents’ perspectives (such as motivational interviewing) are promising in addressing vaccine hesitancy and fostering vaccine uptake [ 53 , 54 ]. From this perspective, future research should explore the impact of increasing parents’ emotional competences.…”
Section: Discussionmentioning
confidence: 99%